Beyond HAT Adaptor: TRRAP Liaisons with Sp1-Mediated Transcription - Bo-Kun Yin (MDPI AG, 2021)
The members of the phosphatidylinositol 3-kinase-related kinase (PIKK) family play vital roles in multiple biological processes, including DNA damage response, metabolism, cell growth, mRNA decay, and transcription. TRRAP, as the only member lacking the enzymatic activity in this family, is an adaptor protein for several histone acetyltransferase (HAT) complexes and a scaffold protein for multiple transcription factors. TRRAP has been demonstrated to regulate various cellular functions in cell cycle progression, cell stemness maintenance and differentiation, as well as neural homeostasis. TRRAP is known to be an important orchestrator of many molecular machineries in gene transcription by modulating the activity of some key transcription factors, including E2F1, c-Myc, p53, and recently, Sp1. This review summarizes the biological and biochemical studies on the action mode of TRRAP together with the transcription factors, focusing on how TRRAP-HAT mediates the transactivation of Sp1-governing biological processes, including neurodegeneration.